Nutrient omission plot technique for yield response, indigenous nutrient supply and nutrient use efficiency estimation of rice (Oryza sativa L.) crop in Andaman & Nicobar Islands - Gangaiah, B (ORYZA-An International Journal of Rice, 2019)
A nutrient omission plot technique (NOPT) study in RCBD with 8 treatments (omission (-) of N, P, K, NP, NK, PK and no nutrient omission)and 3 replicates per treatment was made on rice at Port Blair, Andaman and NicobarIslands during kharif 2015 to ascertain yield response and find out the most crucial nutrient for fertilization.The results revealed that yield response to fertilizers (NPK) was 2.63 t / ha (60.74%). The yield response of P (23.3%) got multiplied by 2.16 and 2.60 times when combined with N and K applications as compared to their individual effects. Indigenous N, P and K supply capacity of the soil was estimated as 70.6, 10.0 and 80.0 kg/ha.Agronomic efficiency (kg grain / kg nutrient applied) was severely limited by P omission (10.13). The economics(Rs/ha) of rice cultivation indicates that omission of NPK & NP fertilizers results in losses. The highest profits realized with no omission (+NPK) were reduced by 52.3% with P omission. Omission of K followed by N and NK has less impact on profits. Rice crop duration got prolonged and shortened under P andN omission while K omission has no such effect.